Systemic School Improvement Interventions in South Africa : Some Practical Lessons from Development Practioners - Khosa, Godwin (Book collections on Project MUSE., 2014)
Looking at two smaller-scale systemic school improvement projects implemented in selected district circuits in the North West and Eastern Cape by partnerships between government, JET Education Services, and private sector organisations, this book captures and reflects on the experiences of the practitioners involved. The Systemic School Improvement Model developed by JET to address an identified range of interconnected challenges at district, school, classroom and household level, is made up of seven components. In reflecting on what worked and what did not in the implementation of these different components, the different chapters set out some of the practical lessons learnt, which could be used to improve the design and implementation of similar education improvement projects. Many of the lessons in this field that remain under-recorded to date relate to the step-by-step processes followed, the relationship dynamics encountered at different levels of the education system, and the local realities confronting schools and districts in South Africa's rural areas. Drawing on field data that is often not available to researchers, the book endeavours to address this gap and record these lessons. It is not intended to provide an academic review of the systemic school improvement projects. It is presented rather to offer other development practitioners working to improve the quality of education in South African schools, an understanding of some of the real practical and logistical challenges that arise and how these may be resolved to take further school improvement projects forward at a wider district, provincial and national scale.